Being spiritual but not religious. (August 2021) - Wixwat, Maria; Saucier, Gerard
Highlights: Spirituality consists of senses of personal connections transcending normal experience. SBNR often have non-standard beliefs and distance themselves from the institutional aspect of religion. There's evidence for distinct and overlapping elements of spirituality & religion. SBNR tend to be higher on openness, extraversion, & neuroticism, lower on agreeableness. Those who identify as Spiritual But Not Religious form a heterogenous population. Abstract : 'Spiritual but not religious' appears to be an increasingly popular self-designation for individuals asked about their religious affiliation. We review scientific literature that helps to unpackage the meaning of the phrase, from conceptual to empirical analyses. Both diversity and ambiguity in how individuals understand the designation and in their motivations for using it are very much evident. Use of the designation appears to have some confound with demographic and cultural background factors. Empirical research does indicate a detectable clear divergence between conventionally religious and mystical tendencies, at least in Western populations that have been the focus of most investigations. But the mystical tendencies that may serve to separate spirituality from religion appear to be themselves heterogeneous, and not necessarily reducible to one disposition.